GLS detrending in nonlinear unit root test - GÜRİŞ, SELAHATTİN (TAYLOR & FRANCIS INC, 2022)
This article proposes to apply the GLS detrending method for the unit root test procedure developed by Kruse [2011. A new unit root test against ESTAR based on a class of modified statistics. Statistical Papers 52 (1):71-85]. The Monte Carlo simulations made indicate that the proposed test is more powerful than the Kruse (2011) test. Using the proposed test, it was examined whether the consumer price index permanent or transitory for 25 countries. According to the results obtained, by using the Kruse test, we find that unit root hypothesis was rejected only in 5 countries while using the GLS Kruse test, the unit root hypothesis was rejected in 15 countries.
Keywords: Unit Root Test; Nonlinearity; GLS Detrending; REAL EXCHANGE-RATES; STAR